2016
DOI: 10.1109/tip.2015.2507942
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Video Synopsis via Scaling Down Objects

Abstract: Video synopsis is an effective technique to provide a compact representation of the original video by removing spatiotemporal redundancies and by preserving the essential activities. Most current approaches for video synopsis will cause collisions among objects, especially when the video is condensed much. In this paper, we present an approach for video synopsis to reduce the collisions. Our approach first shifts active objects along the time axis to compact the original video. Then, the sizes of the objects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 51 publications
1
32
0
1
Order By: Relevance
“…Fig. 9 depicts a set of frames related to two different synopsis outputs obtained by the algorithm proposed in [4], [8], [9], [11], [12] and using our proposed method. Frames that are marked red show sudden appearance and disappearance of objects in the synopsis generated using the method proposed in [4].…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 9 depicts a set of frames related to two different synopsis outputs obtained by the algorithm proposed in [4], [8], [9], [11], [12] and using our proposed method. Frames that are marked red show sudden appearance and disappearance of objects in the synopsis generated using the method proposed in [4].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…It has been observed that, when E(M ) is low by grouping objects (second row), it produces better synopsis outputs. It has been observed that when the synopsis is generated using [4], [8], [9], [11], [12], due to high E(M ), the outputs are often discrete and confusing as compared to our method. We have restricted shifting of objects by grouping, therefore, our method produces longer synopsis with a lower energy difference.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Motion and motion blur are important information that can be used for a machine and robot, especially a surveillance machine/robot [1], to detecting the objects and products [2]- [10]. This paper focuses on a challenging and practical problem: detecting motion blur from a single image captured by a camera installed on a machine.…”
Section: Introductionmentioning
confidence: 99%